Effects of Rhythm Step Training on Foot and Lower Limb Balance in Children and Adolescents with Flat Feet: A Radiographic Analysis - Ji-Myeong Park; Byung-Cho Min; Byeong-Chae Cho; Kyu-Ri Hwang; Myung-Ki Kim; Jeong-Ha Lee; Min-Jun Choi; Hyeon-Hee Kim; Myung-Sung Kang; Kyoung-Bin Min (Medicina, 2024)
Background and Objectives: Owing to the recent reports regarding the efficacy of rhythm step training (RST) in lower limb muscle development and motor skill enhancement, this study aimed to evaluate the effects of RST on foot and lower limb balance in children and adolescents diagnosed with flat feet using radiographic analysis. Materials and Methods: A total of 160 children and adolescents diagnosed with flat feet from a hospital in Seoul were randomly assigned to the general flat feet training (GFFT) (n = 80) or RST (n = 80) group. Patients in both groups exercised for 50 min once a week for 12 weeks. Key variables, such as quadriceps angle (Q-angle), calcaneal pitch angle (CPA), calcaneal–first metatarsal angle (CFMA), and navicular–cuboid overlap ratio (OR) were measured before and after the intervention. Results: Significant improvements in Q-angle (p < 0.001), CPA (p < 0.001), CFMA (p < 0.001), and navicular–cuboid OR (p < 0.001) were observed in the RST group compared to the GFFT group. RST was found to be more effective in normalizing the biomechanical function of the calcaneus and improving lower limb function. Conclusions: RST significantly enhances foot and lower limb balance in children and adolescents with flat feet, suggesting its potential use as an effective intervention for this population. The study did not specifically analyze the effects of various components of rhythm training, such as music, exercise intensity, and frequency, on the outcomes. Further research is needed to determine how each of these elements individually influences the results.